FRI0143 IS PATIENT – PHYSICIAN DISCORDANCE IN ASSESSMENTS OF BURDEN OF RHEUMATOID ARTHRITIS A DETERMINANT OF METHOTREXATE ADHERENCE?. (June 2019) - Bulatovic, Ana; Miketic, Natasa; Bogojevic, Milan; Aligrudic, Svetlana; Medjedovic, Rifat; Tepavcevic, Darija Kisic
Abstract : Background: Accurate assessments of disease activity in rheumatoid arthritis (RA) have a crucial role in establishing disease severity and monitoring response to treatment. There is no objective, numerical measures to estimate RA severity and treatment response. A frequently used means of quantifying the overall perception of disease activity is through an subjective assessment of global disease activity on a visual analogue scale (VAS), both by the patient, and by the physician, as well. The common direction of the discrepancy usually points toward better rating by the physicians than by the patients themselves, leading to potential medication adherence. Objectives: The aims of the study were to explore the presence of disagreement between patients' and physicians' assessment of global disease severity, as well as to investigate the possible correlation between patient – physician discordance in assessments of RA burden and methotrexate adherence. Methods: In the period between May 1 and September 15, 2019, 98 consecutive RA patients who were treated in Clinical center of Montenegro and private clinic "Merkur Nera" randomly chosen Montenegrin clinics were enrolled in this multi-centric cross-sectional study. The inclusion criteria were as follows: age ≥ 18 years, diagnosis of RA of at least 6 months, current methotrexate (MTX) use for at least 1 month (with or without concomitant usage of another RA drugs), and written informed consent. Non-adherence to MTX was defined as ≥1 dose missed against medical advice. The global disease activity is estimated by VAS (using a 0–10 ordinal scale), both by the patient, and by the physician. The differences between groups are assessed using the Mann-Whitney U-test. The correlation between the patient – physician discordance and MTX adherence is evaluated using the Spearman rank correlation. Results: The most of the participants (87.8%) were female with median current age of 57.5 years (range 21-83 years). The median duration of RA was 8 years (range 0-34 years), while the median duration of MTX treatment was 6 years (range 0-26 years). The median value of VAS score estimated both, by the patients and their physician was 5, with no statistically significant difference between these two groups (Z =1.447; p =0.748). The analysis of patient – physician discordance in VAS assessment showed that full agreement is achieved in 76 (77.6%) cases, while in 21 (21, 4%) RA patients their doctors underestimated their self-perception of disease burden. In only one participant, the physician overestimated patient's perception of RA severity. In total sample the self-estimated prevalence of MTX non-adherence was 32.7%. However, the analyses of the frequency of MTX non-adherence in sub-cohorts stratified by the presence of patient – physician discordance in VAS assessment showed that in "concordance group" the prevalence was 26.3% (20 out of 76 RA patients), while in "disconcordance group" the prevalence was 54.5% (12 out of 22 RA patients), with statistically significant difference between these two groups (Z =-5.745; p <0.001). Statistically significant correlation has been observed between presence of patient – physician discordance in VAS assessment and MTX non-adherence (ρ=0, 427; p <0.001). Conclusion: The results of our study have shown that the presence of patient – physician discordance in assessment of global RA activity could deeply influence the MTX adherence in a Montenegrion sample of patients with RA. This finding emphasizes the need to focus on patients' preferences and values to deliver individualized patient-centered care that could potentially enhance adherence and consequently achieved optimally control of disease activity. Disclosure of Interests: None declared